Quorum sensing is crucial to Escherichia coli O157:H7 biofilm formation under static or very slow laminar flow conditions - Lim, Jeesun; Lee, Kang-Mu; Park, Chan Yong; Kim, Han Vit; Kim, Younghoon; Park, Sungsu (Biochip journal, 2016)
Quorum sensing (QS) is defined as a cellto- cell signaling process that collectively regulates the gene expression of bacteria via small signaling molecules called autoinducers (AIs). It was reported that QS-regulated gene expression in Pseudomonas aeruginosa failed to occur at a high Reynolds number (Re= 3,000), since AI-2, a secreted interspecies signaling molecule, was washed away and so could not reach the minimum concentration required for QS. In this study, we describe the effects of flow speed on QS-stimulated biofilm formation in Escherichia coli O157:H7 inside a very thin microchannel (3 cm×1 cm×45 μm). In microtiter plates, the wild-type strain produced high amounts of exopolysaccharide, whereas its QS mutants ΔluxS and ΔlsrK , defective in AI-2 production and phosphorylation, made less exopolysaccharide. Confocal laser scanning microscopy showed that at a flow rate of 1 μL/min the wild-type strain formed rounded biofilms, whereas such biofilms formed by the QS mutants were fewer and thinner. At a flow rate of 10 μL/min, none of the tested strains formed mature biofilms. Our results suggest that QS is essential in the biofilm maturation under static or very slow laminar flow conditions where the biofilm signal can be easily accumulated and transported to the sessile cells.